Wind Tower Vibration Controlled by a Pendulum TMD using Genetic Optimization: Beam Modelling. (2017) - Colherinhas, Gino B.; Shzu, Maura A.M.; Avila, Suzana M.; Morais, Marcus. V.G. de
Abstract: This paper models a wind turbine tower and passive pendulum TMD with finite element using the resources and capabilities of commercial software ANSYS. Although structural control of high slender towers using pendulum TMDs is widely studied in literature, it was not found yet studies modelling the pendulum TMD with ANSYS. Using a Genetic Algorithms (GA), this work optimize the parameters of pendulum TMD (stiffness, damping, length and mass ratio) installed on the top of a wind turbine tower. The aim of this paper is to evaluate the differences between the responses obtained through finite element and analytical 2 degree of freedom (2DOF) models. Also it is investigated the influence of the model adopted on TMD parameters optimization results. It was verified a little difference between the frequency response functions obtained through beam and analytical 2DOF models, using the same TMD parameters in both cases.